2018
DOI: 10.21704/rea.v17i1.1168
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de cuantificación de plomo en suelos de parques recreacionales de la ciudad de Lima - Perú

Abstract: ResumenLos Grandes Parques de Lima Metropolitana (GPLM) son áreas verdes donde habitan diversidad de especies de origen vegetal y animal. Los GPLM, áreas recreacionales localizadas en la cuenca del río Rímac considerados en este estudio fueron los siguientes: Bosque El Olivar (12º06´04´´S, 77º02´05´´O), Campo de Marte (12º04´06´´S, 77º02´29´´O), Pentagonito (12º06´01´´S, 76º59´35´´O), Zoológico de Huachipa (12º00´52´´S, 76º53´52´´O), Las Leyendas (12º07´14´´S, 77º05´12´´O) y Kennedy (12º07´18´´S, 77º01´49´´O).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…Most of these values are above the environmental quality standard established for park floors (i.e., 140 ppm). These results confirm findings of a previous research carried out in the Zoological Park of Huachipa, by Tello et al (2018) who observed that soils in the park, specifically in the area of the bird forest, are contaminated by lead. This is likely due to sediments left by waters of the Rímac River, which tends to overflow and flood this area (Tello et al, 2018).…”
Section: Initial Lead Content In the Study Areasupporting
confidence: 92%
See 2 more Smart Citations
“…Most of these values are above the environmental quality standard established for park floors (i.e., 140 ppm). These results confirm findings of a previous research carried out in the Zoological Park of Huachipa, by Tello et al (2018) who observed that soils in the park, specifically in the area of the bird forest, are contaminated by lead. This is likely due to sediments left by waters of the Rímac River, which tends to overflow and flood this area (Tello et al, 2018).…”
Section: Initial Lead Content In the Study Areasupporting
confidence: 92%
“…A possible explanation for our findings lies in the use of water from the Rímac River by the park managers to irrigate the plantations around the Bird Forest on 4 occasions. Because, the sediments of the Rímac River are contaminated by lead, using the river water for irrigation could have contaminated our study site as suggested by Tello et al (2018). Moreover, the damping effect of soils and its high organic matter content (4.89%) may also contribute to higher lead concentrations.…”
Section: Initial Lead Content In the Study Areamentioning
confidence: 97%
See 1 more Smart Citation
“…However, due to the raw materials used, it can contain significant contents of heavy metals [18,[20][21][22][23][24]. It is known that green spaces with arboreal vegetation in an urban environment retain heavy metals in the foliage due to the precipitation of atmospheric dust produced mainly by the use of fossil fuels by vehicular traffic [7,[25][26][27][28][29][30][31]. It is also known that cattle manure contains significant amounts of some heavy metals [32][33][34][35][36] which is due to the fact that cattle feed has nutrients fortified with these elements and that, in some cases, the quantities supplied are greater than the absorption in the digestive process, whereby these are excreted [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Los suelos y áreas verdes que son regados por el agua del río Surco contienen metales como arsénico, plomo, mercurio, fosfatos y nitratos principalmente, así como también coliformes fecales (Tello, Jave y Guerrero, 2018). Ello se debe a que el agua presenta los mismos indicadores los cuales al entrar en continuo contacto con el suelo por el mismo riego; algunos se infiltran y otros se acumulan hasta afectar su calidad perenne.…”
Section: Contaminación Del Río Surco Y Sus Efectosunclassified